Adsorptive Removal of Crystal Violet from Aqueous Solutions using Agarose Gel as a Natural Adsorbent : Penghilangan Kristal Violet dari Larutan Air Menggunakan Gel Agarosa sebagai Adsorbent Alami - Gatea, Azhar Hameed; Ali, Alaa Mohammed; Ajel, Aseer shakir (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Wastewater containing synthetic dyes requires sustainable treatment solutions. Specific Background: Agarose gel, a natural polysaccharide with abundant hydroxyl groups, offers strong affinity toward cationic dyes such as crystal violet. Knowledge Gap: Limited studies have comprehensively assessed how pH, contact time, and initial dye concentration jointly influence adsorption onto agarose while comparing advanced three-parameter isotherm models. Aims: This study investigates the adsorption of crystal violet onto agarose gel and evaluates equilibrium behavior using Langmuir, Sips, and Radke–Prausnitz models. Results: Adsorption reached 95 percent removal under mildly alkaline conditions (pH 9) within 50 minutes, with higher initial concentrations reducing removal due to surface saturation. The Sips and Radke–Prausnitz models showed superior fitting (R² > 0.998), indicating heterogeneous and cooperative adsorption, while Langmuir was adequate only at low concentrations. Novelty: This research is among the first to directly compare the Sips and Radke–Prausnitz models for agarose-based adsorption of crystal violet. Implications: Agarose demonstrates strong potential as a low-cost, biodegradable adsorbent for green wastewater treatment systems, providing insights for future development of natural polymer-based remediation technologies. Highlights• High adsorption efficiency of agarose under alkaline conditions• Superior fitting of Sips and Radke–Prausnitz models• Potential of agarose as a green adsorbent for dye removal Keywords: Agarose, Adsorption Isotherm, Crystal Violet, Natural Adsorbent, Wastewater Treatment